PEDAGOGICAL CONDITIONS OF EDUCATION OF WORLDVIEW CULTURES OF STUDENTS IN EXTRACURRICULAR WORK (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the analysis of the notion "world view culture of a person”. The favourable pedagogical conditions for the solution of the problems of the world outlook development within the students of the higher schools are concidered and analysed.